2022
DOI: 10.1002/ps.7243
|View full text |Cite
|
Sign up to set email alerts
|

Licorice strips enhance predator‐mediated biological control in China's cotton crop

Abstract: BACKGROUND Habitat management such as field‐ or farm‐level diversification can conserve arthropod natural enemies, enhance biological pest control and lower (or suspend) insecticide use in agricultural crops. These approaches however have been underexploited to manage the aphid Aphis gossypii in cotton cropping systems of Xinjiang, China. In this study, we investigated whether the presence of licorice (Glycyrrhiza uralensis) at the field edge benefits generalist predator abundance and aphid biological control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…However, these plants support a diverse population of natural enemies of aphids, such as ladybeetles. 76,77 By using repellent substances to drive Aphis gossypii onto these plants, we provide prey for these natural enemies and promote their population increase, possibly contributing to control of the Aphis gossypii population. Consequently, we believe that use of repellents to manage Aphis gossypii in cotton fields should promote regional management of Aphis gossypii.…”
Section: Discussionmentioning
confidence: 99%
“…However, these plants support a diverse population of natural enemies of aphids, such as ladybeetles. 76,77 By using repellent substances to drive Aphis gossypii onto these plants, we provide prey for these natural enemies and promote their population increase, possibly contributing to control of the Aphis gossypii population. Consequently, we believe that use of repellents to manage Aphis gossypii in cotton fields should promote regional management of Aphis gossypii.…”
Section: Discussionmentioning
confidence: 99%
“…Intercropping regularly lowers herbivore abundance and lifts numbers of invertebrate predators or parasitoids, as evidenced in peanut × maize, 38 onion × cabbage, 39 wheat × mungbean, 40 and wheat × rape systems. 41 It is commonly assumed that enhanced plant diversity translates in higher natural enemy numbers, [42][43][44][45] yet empirical work in different systems yields rather inconsistent patterns. In cotton systems, different intercrops reduce Aphis gossypii infestation pressure 46 enhanced (crop) diversity or by providing (food, non-food) resources to resident natural enemies.…”
Section: Discussionmentioning
confidence: 99%
“…The predatory ladybeetle community mainly includes Hippodamia variegata (Goeze), Propylaea quatuordecimpunctata (Linnaeus), Oenopia conglobata (Linnaeus), Coccinella tredecimpunctata Linnaeus, and Stethorus punctillum Weise. Survey results of field population density showed that H. variegata was abundant in cotton fields in many areas of Xinjiang [ 18 , 19 , 20 ], and was a dominant predator [ 21 , 22 ]. Regarding aphid parasitoids in the cotton fields of Xinjiang, the population dynamics and parasitism rate of aphids have been investigated and the composition of the aphid parasitoid community has been determined (65% primary parasitoids, 35% hyperparasitoids).…”
Section: Introductionmentioning
confidence: 99%